Green Growth Towards Sustainable Development in Vietnam - Đạt, Trần Thọ; Trường, Đinh Đức (VNU Journal of Science: Social Sciences and Humanities; Vol 29 No 4, 2013)
Abstract: Nowadays, growth model towards sustainable development widely recognized by international community is green growth. However, the awareness, understanding and application of green growth are still in process of formation for most countries. Promoting green growth inVietnamis not only suitable for the current economic integration process, but more importantly it comes from the requirement of internal economy for growth model transformation.Vietnam, after three decades of rapid growing is now facing several development issues such as low economic growth quality, weak competitiveness, low efficiency, social inequality, natural resource depletion, environmental pollution and climate change. In this context, green growth can be a potential solution to these problems and helpsVietnamgoing towards sustainable development This paper aims at analyzing basic dimensions of green growth in Vietnam by focusing on following contents (i) development context in Vietnam; (ii) reasons for the selection of green growth model in Vietnam; (iii) commitments and steps of Vietnam towards green growth; (iv) opportunity and the challenge of Vietnam towards green growth model and (v) policy implications for green growth in Vietnam. This paper uses the secondary data gathered from officially international and domestic sources inVietnam. Economic growth is a critical goal of all nations. After more than two decades of embracing economic reforms,Vietnamhas now joined the group of medium income   countries. The paper analyses the relationship between green growth and quality of sustainable development inVietnam. This paper aims at analyzing basic dimensions of green growth in Vietnam by focusing on following contents (i) development context and reasons for the selection of green growth model in Vietnam; (ii) commitments and steps of Vietnam towards green growth; (iii) opportunities and challenges of Vietnam towards green growth model and (v) policy implications for green growth in Vietnam. This paper uses the secondary data gathered from officially international and domestic sources inVietnam. Keywords: Green growth, climate change, energy efficiency, sustainable development, Vietnam Green Growth Strategy.